Modulation of Immune System Function by Measles Virus Infection: Role of Soluble Factor and Direct Infection - Fujinami, Robert S. (American Society for Microbiology, 1998)
Measles virus infection can result in a variety of immunologic defects. We have begun studies to determine the basis for the lack of immune responsiveness to antigen and mitogen following infection. Here we present data showing that Epstein-Barr virus-transformed B-cell lines infected with measles virus produce a soluble factor that can inhibit antigen-specific T-cell proliferation and inhibit the proliferation of uninfected B cells. The soluble factor was neither interleukin-10, transforming growth factor β, nor alpha/beta interferon. B cells infected with measles virus or treated with the soluble factor were unable to present antigen to T cells in a manner that supported antigen-specific proliferation. This could represent one mechanism of how measles virus limits T-cell expansion. However, we found that once CD4(+) or CD8(+) T cells were activated, their cytolytic activity was intact whether infected with measles virus or treated with soluble factor. Thus, while slow to be generated these cytoxic cells could participate in viral clearance.